Diagnostic Significance of Metagenomic Next-Generation Sequencing for Community-Acquired Pneumonia in Southern China - Liu, Hanying; Zhang, Ying; Chen, Guiyang; Sun, Shenghua; Wang, Jiangang; Chen, Fengyi; Liu, Chun; Zhuang, Quan (Frontiers in Medicine, 2022)
Background: The morbidity and mortality of community-acquired pneumonia are relatively high, and many pneumonia pathogens cannot be identified. As a new pathogen detection technology, mNGS has been applied more and more clinically. We aimed to evaluate the diagnostic significance of metagenomic next-generation sequencing (mNGS) for community-acquired pneumonia (CAP) in the south of China. Methods: Our study selected CAP patients visiting our hospital from May 2019 to April 2021, and pathogens in bronchoalveolar lavage fluid (BALF) specimens were detected using mNGS. mNGS group: tested by both mNGS and BALF culture; control group: tested only by BALF or sputum culture. The diagnostic performance of pathogens and the antibiotic adjustments were compared within mNGS group. Results: The incidence of acute respiratory distress syndrome (ARDS) was 28.3% in the mNGS group and 17.3% in the control group. Within the mNGS group, the positive rate of pathogen detection by mNGS was 64%, and that by BALF culture was 28%. Pathogens detected by mNGS were consisted of bacteria (55%), fungi (18%), special pathogens (18%), and viruses (9%). The most detected pathogen by mNGS was Chlamydia psittaci. Among the pathogen-positive cases, 26% was not pathogen-covered by empirical antibiotics, most of which were made an antibiotic adjustment. Conclusions: mNGS can detect pathogens in a more timely and accurate manner and assist clinicians to timely adjust antibiotics. Therefore, we recommend mNGS for the complementary diagnosis of severe pneumonia or complicated infections.